Meningkatkan Penalaran Kritis Siswa Melalui Metode PBL Pada Pak ateri Aku Pribadi Yang Unik Kelas IV SDN 27 Seledok - Murni Murni; Anselmus Yata Mones Dosen (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
. The background to this research highlights the lack of effectiveness of the learning methods applied in class IV phase B for Catholic Religious Education (PAK) subjects in stimulating the development of students' critical reasoning. In facing this challenge, classroom action research was carried out by applying the Problem Based Learning (PBL) Learning Model. This research aims to improve students' critical reasoning abilities and achieve the set learning targets. With quantitative methods, research was carried out through two cycles. The results of the first cycle showed an increase in students' critical reasoning by 73.5%, with a number of students reaching advanced and proficient levels. The second cycle showed significant improvement, with students' critical reasoning reaching 86%. Learning outcomes also increased, with more students reaching advanced levels. The implications of these findings illustrate that the application of Problem Based Learning is effective in improving students' critical reasoning and achieving the desired learning targets.